Dually-functional riboflavin macromolecule as a supramolecular initiator and reducing agent in temporally-controlled low ppm ATRP - I. Zaborniak; P. Chmielarz (eXPRESS Polymer Letters)
A novel supramolecular riboflavin-inspired macroinitiator was prepared for the first time by transesterification methodology and used as the multifunctional vitamin-B2 core to synthesize PBA brushes using different low ppm atom transfer radical polymerization (ATRP) approaches. Firstly the macromolecular initiator was successfully applied as a dually-functional structure, which simultaneously acts as a reducing agent in activator regeneration by electron transfer (ARGET) ATRP. Subsequently simplified electrochemically mediated ATRP of BA with different conditions was carried out for the preparation of well-defined riboflavin-based polymer brushes. Polymerizations were characterized in a well-controlled manner, affording polymers with a narrow dispersity (Ð = 1.22–1.25). Four-arms polymers were also received by an approach never described before – temporally-controlled multi-step seATRP under constant current conditions, giving precisely-defined polymer brushes (Ð = 1.26) with preserved chain-end functionality (DCF < 1%), despite stopping and restarting the polymerization. The solvolysis results indicate that all chains grow to equal lengths (Ð < 1.17), which shows the precisely controlled characteristic of seATRP. 1H NMR analysis confirms the formation of new vitamin B2-inspired polymers. In connection with the preserved riboflavin functionality and additional functional chains, these innovative macromolecules may find applications, e.g. as drug delivery systems.